Enatioselective Rotation of Chiral Particles by Azimuthally Polarized Beams. Issue 10 (28th June 2022) - Li, Manman; Chen, Xu; Yan, Shaohui; Zhang, Yanan; Yao, Baoli
Abstract : The chirality‐dependent forces can offer new possibilities for passive optical separation and identification of chiral particles, which opens great opportunities to develop the technologies of pharmaceutics, chemicals, and biomedicine. Here, a robust enantioselective rotation of subwavelength chiral particles using lateral optical forces induced by a tightly focused azimuthally polarized beam is demonstrated. Although this focused field carries neither optical orbital angular momentum nor optical chirality, the lateral optical force can rotate the particle with opposite chirality around opposite directions, achieving an effective optical enantioseparation. Such a counterintuitive phenomenon is closely related to the transformation of the magnetic spin angular momentum of the focused field into the mechanical orbital angular momentum of the particle. In addition, the particle with different chirality parameters will be trapped in different orbits while with opposite chirality trapped in the same orbit, meanwhile its rotation direction is determined by the sign of the chirality parameter, which can realize an efficient chiral identification of single particles. The investigations may open up a new path toward light‐induced rotation or probing of objects with different chirality parameters. Abstract : The tightly focused azimuthally polarized beam carries neither optical chirality nor orbital angular momentum (OAM), but can trap particles with different magnitude of chirality parameters on different orbits, while trap particles with opposite chirality on the same orbit but drive them rotate towards opposite directions, achieving an effective optical separation of chiral particles and chiral identification of single particles.